2013
DOI: 10.1074/jbc.m113.521799
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Interacts with Derlin-1 and Promotes Ubiquitination and Degradation of Cyclooxygenase-2 via Collaboration with p97 Complex

Abstract: Background: Caveolin-1 assists in COX-2 degradation through the proteasome pathway. Results: Caveolin-1 enhances interactions among COX-2, Derlin-1, and the p97-Ufd1 complex and assists in COX-2 retrotranslocation and ubiquitination. Conclusion: Caveolin-1 is a cofactor facilitating COX-2 degradation via a Derlin-1-p97 pathway. Significance: Results represent a novel model for Derlin-1-mediated N-glycosylated protein degradation facilitated by caveolin-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In the absence of its major substrate AA, COX-2 undergoes continuous turnover by shuttling from the endoplasmic reticulum to the cytosol via the ER-associated degradation (ERAD) pathway, where it is subsequently degraded by the proteasome (9). Degradation of COX-2 in the proteasome is preceded by its polyubiquitination (10), and was recently shown to be facilitated by caveolin-1 (11) and also through its interaction with the GPCRs, prostaglandin E 1 (EP 1 ), and ␤ 1 adrenergic (␤ 1 AR) receptors (12,13). Here we set to explore whether, in addition to the known negative feedback loop between angiotensin II and COX-2, there is an additional mechanism for down-regulating COX-2 expression by AT 1 , and to identify the domains of the receptor that mediate this effect.…”
mentioning
confidence: 99%
“…In the absence of its major substrate AA, COX-2 undergoes continuous turnover by shuttling from the endoplasmic reticulum to the cytosol via the ER-associated degradation (ERAD) pathway, where it is subsequently degraded by the proteasome (9). Degradation of COX-2 in the proteasome is preceded by its polyubiquitination (10), and was recently shown to be facilitated by caveolin-1 (11) and also through its interaction with the GPCRs, prostaglandin E 1 (EP 1 ), and ␤ 1 adrenergic (␤ 1 AR) receptors (12,13). Here we set to explore whether, in addition to the known negative feedback loop between angiotensin II and COX-2, there is an additional mechanism for down-regulating COX-2 expression by AT 1 , and to identify the domains of the receptor that mediate this effect.…”
mentioning
confidence: 99%
“…Therefore, studies are needed to identify this type of cancer cell, and the signaling molecules that are specifically involved in cancer progression. Derlin-1, a partner of the p97 ATPase complex, was initially reported to mediate the elimination of misfolded proteins from the endoplasmic reticulum (ER) and retrotranslocation of proteins into the cytosol [3][4][5]. Accumulating evidence has strongly implicated that Derlin-1 plays an important and multifaceted role in cancer progression [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Finally, in events involving EDEM, ERp57, OS-9, XTP3-B, and the HRD1-SEL1L ubiquitin ligase complex (39,44), a trimmed and unfolded COX-2 is translocated to the cytosol for ubiquitination and proteasomal degradation (25,28,29,32,35). The slow glycosylation observed with KDEL huCOX-2 suggests that the rate-limiting step in ERAD of COX-2 is post-translational glycosylation of Asn-594 in the ER.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…We have reported that properly folded COX-2 can be degraded via two distinct pathways including AA turnover-dependent degradation and constitutive degradation involving the ER-associated degradation (ERAD) pathway (29,30). Others have shown that COX-2 can be ubiquitinated and degraded through the 26 S proteasome (32,35). ERAD involves a series of related but different events that include detecting misfolded proteins bound for degradation, translocating these proteins into the cytosol, and degrading the proteins via the 26 S proteasome (for recent reviews see, Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation